UUDAT based on the modular multilevel converter and diode bridges for high‐voltage DC application. Issue 16 (17th December 2018) - Zhou, Meng; Xiang, Wang; Zuo, Wenping; Lin, Weixing; Wen, Jinyu; Xie, Zhujun
Abstract : Conventional unidirectional DC/DC converters for high‐voltage direct current application employ DC/AC/DC technology and suffer from high converter cost and power loss. To solve these issues, a unidirectional step‐up DC–DC autotransformer (UUDAT) is studied. UUDAT is composed of the series connection of diode bridges and voltage source converters. Topologies of UUDAT is detailed. The harmonic and uncontrollability issues are discussed. Control and the possible application scenario for UUDAT are proposed. The ways of dimensioning the voltage and power rating of the components in UUDAT are studied. Extensive simulations on the power system level verified the technical feasibility of UUDATs.